The European External Action Service: a new institutional framework for EU development cooperation - Mark Furness (Deutsches Institut für Entwicklungspolitik (DIE), 2010)
Development cooperation will be central to the external policy of the post-Lisbon Treaty EU. Measuring up to the letter and spirit of the Lisbon Treaty requires strengthening the European Union (EU) as a development actor, while ensuring that development policy is flexible enough to respond to – but not be dominated by – the demands of a changing foreign policy environment. The new European External Action Service (EEAS) will be the key EU external policy institution and will play an important role in EU development policymaking. Public debates accompanying the EEAS' roll-out have highlighted four crucial areas where the new Service can help improve the effectiveness of EU development policy: promoting policy coherence for development, facilitating coordination among actors, fostering professionalism and building legitimacy. All these elements require member states to continue to support the EU external policy integration process, stronger institutional measures to protect development objectives, and strong involvement from the European Commission and Parliament. Improving the coherence, coordination, professionalism and legitimacy of development policy has great potential for increasing the EU's global influence, both as a development actor and as a foreign policy actor.
Keywords: 330